Cardiac autonomic modulation of children with down syndrome - Carvalho, Tatiana Dias de; Abreu, Luiz Carlos de; Mustacchi, Zan; Marques Vanderlei, Luiz Carlos [UNESP]; Godoy, Moacir Fernandes; Raimundo, Rodrigo Daminello; Ferreira Filho, Celso; Silva, Talita Dias da; Guilhoto, Laura; Perico, Viviane; Finotti, Vivian Ribeiro; Ferreira, Celso (Springer, 2015)
The aim of this study is to analyze the autonomic modulation in children with Down syndrome (DS). The study was conducted with a convenience sample of children with DS and without heart disease, from the Genetics Clinic of the Hospital Infantil Darcy Vargas and APAE So Paulo, So Paulo, SP, Brazil. The control group was matched for sex and age. The analysis of autonomic modulation was performed using the indices of heart rate variability (HRV). The children remained in the supine position with spontaneous breathing for 20 min. Heart rate was recorded beat-to-beat. HRV analysis was performed in time and frequency domain. For data analysis, we used Student's t test: unpaired and Mann-Whitney. It was considered statistically significant at p < 0.05. From 75 children with DS, 50 were excluded, a total of 25 children [16 boys, 8.6 (1.4) years] participated in this study, and the control group also consisted of 25 children [16 boys, 9.0 (1.2) years] without the syndrome. The BMI of the volunteers with DS was higher than the controls [19.1 (2.9) vs. 15.8 (1.2), p < 0.0001]. There were differences between groups in the indices in frequency domain: LFms(2) [1242.1 (788.25) vs. 786.44 (481.90), p = 0.040], LFun [69.104 (11.247) vs. 57.348 (11.683), p = 0.0004], HFun [30.896 (11.247) vs. 42.520 (11.634), p = 0.0004] and LF/HF [2.594 (1.104) vs. 1.579 (0.9982), p = 0.0004]. No differences were observed in time domain indices. The results indicate increased indices representing the sympathetic branch of the autonomic nervous system and those that indicate the overall modulation in children with DS.
Keywords: Autonomic nervous system; Children; Heart rate variability; Down syndrome